ELECTROOXIDATION TECHNOLOGY FOR THE REMOVAL OF ORGANIC POLLUTANTS FROM INDUSTRIAL WASTEWATER (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
The removal of organic pollutants from industrial wastewater is a critical environmental issue, as conventional methods often struggle to effectively treat complex industrial effluents. Electrooxidation technology has emerged as an effective solution for degrading a wide range of organic contaminants, including dyes, pharmaceuticals, and other industrial chemicals.